2019
DOI: 10.1016/j.athoracsur.2019.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin-1 Is a Useful Diagnostic Marker for High-Grade Lung Neuroendocrine Tumors

Abstract: Background. Stathmin-1 regulates microtubule dynamics and is associated with malignant phenotypes in non-small cell lung cancer (NSCLC). This study evaluated its diagnostic value for differentiating between NSCLC and high-grade lung neuroendocrine tumor (HGNET).Methods. Stathmin-1 protein expression was assessed by immunohistochemistry in 414 NSCLC (305 adenocarcinoma [AD], 102 squamous cell carcinoma [SCC], 7 largecell carcinoma), 5 typical carcinoid (low-grade lung neuroendocrine tumor), and 34 HGNET (17 sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…High STMN1 expression is also associated with cancer progression and chemoresistance in lung squamous cell carcinoma (28). Similar to our results, Shimizu et al reported that all 17 LCNEC samples expressed a high level of STMN1 in their study, indicating that STMN1 might be a potential diagnostic marker for high-grade lung neuroendocrine tumors (29). Second, we identified the Wnt signaling pathway, which plays a role in the development of lung cancer (30).…”
Section: Discussionsupporting
confidence: 89%
“…High STMN1 expression is also associated with cancer progression and chemoresistance in lung squamous cell carcinoma (28). Similar to our results, Shimizu et al reported that all 17 LCNEC samples expressed a high level of STMN1 in their study, indicating that STMN1 might be a potential diagnostic marker for high-grade lung neuroendocrine tumors (29). Second, we identified the Wnt signaling pathway, which plays a role in the development of lung cancer (30).…”
Section: Discussionsupporting
confidence: 89%
“…High STMN1 expression is also associated with cancer progression and chemoresistance in lung squamous cell carcinoma [28]. Similar to our results, Shimizu et al reported that all 17 LCNEC samples expressed a high level of STMN1 in their study, indicating that STMN1 might be a potential diagnostic marker for high-grade lung neuroendocrine tumors [29]. Second, Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 88%
“…Stathmin-1 is associated with malignancy in NSCLC and is used in the differential diagnosis with high-grade LNETs. Stathmin-1 is a protein responsible for cancer cell survival, used in the signal transduction of malignant cells, and found at high levels in high-grade lung neuroendocrine tumors (HG-LNETs), being used for differential diagnosis between NSCLC and SCLC and LCNEC (47).…”
Section: Biological Landscape Of Lung Neuroendocrine Tumors (Lnets)mentioning
confidence: 99%